1997
DOI: 10.1016/s0304-3959(97)00036-5
|View full text |Cite
|
Sign up to set email alerts
|

Adrenosensitivity of injured afferent neurons does not require the presence of postganglionic sympathetic terminals

Abstract: Nerve injury sometimes triggers neuropathic pain states that are exacerbated by sympathetic efferent activity. A classic example is causalgia. The mechanism of coupling between sympathetic efferent activity and the afferent discharge responsible for pain sensation is a subject of controversy. Some authors hold to the 'direct coupling hypothesis' which proposes that noradrenaline (NA), released from sympathetic varicosities, acts directly on alpha-adrenoreceptors located in the membrane of injured primary affer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…C‐fibres of the skin of normal rats do not respond to NE but NE causes an excitation of the neurons in rats with inflammation (31). Comparable effects were also seen in other models (46–49). In the present experiments, care was taken to avoid any inflammation of the dura mater and the basal levels of CGRP were low, indicating non‐stimulated conditions.…”
Section: Discussionsupporting
confidence: 68%
“…C‐fibres of the skin of normal rats do not respond to NE but NE causes an excitation of the neurons in rats with inflammation (31). Comparable effects were also seen in other models (46–49). In the present experiments, care was taken to avoid any inflammation of the dura mater and the basal levels of CGRP were low, indicating non‐stimulated conditions.…”
Section: Discussionsupporting
confidence: 68%
“…Sympathetic activity may generate pain under certain pathological conditions. In sympathetically maintained pain cases, the receptors at the primary afferents can change and become sensitive to adrenergic substances such as norepinephrine [ 13 14 ]. It was reported that SGB is effective to reduce pain related to temporal arteritis and sympathetic maintained headache and orofacial pain [ 15 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The injured and migrated cells consequently release various neuroactive mediators, which infiltrate the tissues and act at corresponding receptors on the surface of afferent nerve terminals in NAUs via the axon reflex [17]. Meanwhile, tissue injury results in plastic changes in peripheral primary afferents, which develop synapse-like contacts with postganglionic sympathetic nerve varicosities, where NA release acts on α -adrenoceptors on afferent nerve terminals of NAUs [22, 23]. …”
Section: Biochemical Reactions Of Nausmentioning
confidence: 99%